2021
DOI: 10.1155/2021/8573897
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Rotary Tillage Blade Design for Reduced Torque and Energy Requirement

Abstract: A rotary cultivator is a primary cultivating machine in many countries. However, it is always challenged by high operating torque and power requirement. To address this issue, biomimetic rotary tillage blades were designed in this study for reduced torque and energy requirement based on the geometric characteristics (GC) of five fore claws of mole rats, including the contour curves of the five claw tips (GC-1) and the structural characteristics of the multiclaw combination (GC-2). Herein, the optimal blade was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…During soil engagement, the curves and crests on the biomimetic rotary tiller blades enhanced penetration and cutting into the soil with minimal resistance, thus the reduced torque and specific power requirements. Similar observations were made by Yang et al (2021), who experimented on a blade with simulated five profile curves of the mole rat's claws. In addition, the bionic modifications on the tool improved stress distribution on the soil cutting surfaces, thus optimising its structural capability (Guo et al, 2009).…”
Section: Torque and Power Requirementssupporting
confidence: 75%
See 1 more Smart Citation
“…During soil engagement, the curves and crests on the biomimetic rotary tiller blades enhanced penetration and cutting into the soil with minimal resistance, thus the reduced torque and specific power requirements. Similar observations were made by Yang et al (2021), who experimented on a blade with simulated five profile curves of the mole rat's claws. In addition, the bionic modifications on the tool improved stress distribution on the soil cutting surfaces, thus optimising its structural capability (Guo et al, 2009).…”
Section: Torque and Power Requirementssupporting
confidence: 75%
“…They realised that the biomimetic blades required lower torque than the universal blade. Yang et al (2021) simulated the convex contour curves of the five claws of a mole rat on biomimetic rotary tiller blades. They revealed that the geometrical structure of the five foreclaws reduced the torque requirements during soil-cutting by up to 13.99%.…”
Section: Introductionmentioning
confidence: 99%
“…al. 4 also reported that an increase in the operating depth leads to an increase in the torque requirement, which in turn results in an increase in the power requirement.…”
Section: Discussionmentioning
confidence: 95%
“…al. 4 developed rotary tillage blades inspired by the geometric attributes of the ve foreclaws of mole rats, aiming to minimize torque and energy requirements. They discovered that bioinspired blades required less torque than conventional blades.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have extensively researched the operational performance of blades used in agricultural machinery in soil environments. Some researchers have explored altering particle trajectories by designing blades of different shapes to influence the movement of soil particles along predetermined paths [12][13][14][15]. Others have investigated the cutting and scattering processes of blades to uncover underlying patterns of particle motion [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%